Thiodolf Rein, Hermann Lotze and the rise of empiricism in Finland - Kallio Lauri (The Swedish Society for the History of Science and Ideas, 2022)
The paper addresses Thiodolf Rein’s (1838–1919) view of empiricist philosophies, which arrived in Finland in the second half of the nineteenth century. Rein was the key figure of Finnish philosophy towards the end of the nineteenth century. His philosophy was strongly influenced by Hermann Lotze (1817–1881), probably the most distinguished German philosopher of the time. In his main work, "Försök till en framställning af psykologin eller vetenskapen om själen" (Attempt at a presentation of psychology, or the science of the soul, 1876–1891), Rein attempts to reconcile modern natural science and its empirical methodology with idealist metaphysics. His chief concern is to refute the claim that the results of natural science corroborate materialism. Whereas Lotze had only shortly commented on Charles Darwin’s theory of evolution, Rein attempts to integrate Darwin’s theory into his idealist metaphysics. Besides philosophy, Rein’s arguments had also implications for broader political and cultural issues of the time.